Resistance to antibody neutralization in HIV-2 infection occurs in late stage disease and is associated with X4 tropism - Marcelino, José Maria (2013)
This is a non-final version of an article published in final form in AIDS. 28 November 2012 - Volume 26 - Issue 18 - p 2275–2284